Screening of Antioxindant Activity of Fruit Peel and Stem Bark Extracts od Garcinis mangostana L Using the 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) Method - La Eddy; Nunun Ainun Putri Sari Banun Kaliky (Biofaal Journal, 2026)
Mangosteen stem bark and rind are known to contain various bioactive compounds such as xanthones, flavonoids, and polyphenols, which can function as antioxidants. To measure the level of antioxidant ability of stem bark and mangosteen fruit peel extracts, one method that is often used is the 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) method. The purpose of this study was to determine the antioxidant activity of stem bark and fruit peel extracts of Garcinia mangostana L using the 2,2- Diphenyl-1-Picrylhydrazyl (DPPH) method. Samples of stem bark and fruit peel were extracted by maceration method after that followed by antioxidant activity testing with DPPH method. The results showed that the stem bark extract of G. mangostana L. had an LC50 value of 42,95 ppm, while the fruit peel extract showed a lower LC50 value of 12,13 ppm, indicating that both had very strong antioxidant activity. The content of bioactive compounds such as phenolics, flavonoids, and xanthones is the main cause of the high antioxidant activity, making G. mangostana L. stem bark and fruit peel extracts potential therapeutic agents in the prevention and treatment of oxidative stress-related diseases.